2015
DOI: 10.1088/0953-2048/28/10/105015
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz emission from a stack of intrinsic Josephson junctions in Pb-doped Bi2Sr2CaCu2O8+δ

Abstract: We observe continuous terahertz-wave emission from a stack of intrinsic Josephson junctions made of slightly Pb-doped Bi 2 Sr 2 CaCu 2 O 8 d + . We investigate how Pb doping affects the c-axis current-voltage and emission characteristics. The terahertz emission spectra are measured by Fourier-transform infrared spectroscopy and reveal that the emission frequency is remarkably increased by Pb doping, an effect that we attribute to cavity resonance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…The corresponding current densities are about 220 A/cm 2 . Although this value is higher than switching current densities reported earlier [25,28,32,69,70] the fact that the switching current is nearly temperature independent over a large range of bath temperatures suggests that the actual critical current I c and the corresponding current density j c must be much higher. For slightly overdoped samples, measurements on small IJJ stacks revealed j c of at least 2 kA/cm 2 at 4.2 K, which would correspond to a critical current of 0.8 A for our stack [75].…”
Section: Sample Preparation and Measurement Techniquescontrasting
confidence: 57%
See 1 more Smart Citation
“…The corresponding current densities are about 220 A/cm 2 . Although this value is higher than switching current densities reported earlier [25,28,32,69,70] the fact that the switching current is nearly temperature independent over a large range of bath temperatures suggests that the actual critical current I c and the corresponding current density j c must be much higher. For slightly overdoped samples, measurements on small IJJ stacks revealed j c of at least 2 kA/cm 2 at 4.2 K, which would correspond to a critical current of 0.8 A for our stack [75].…”
Section: Sample Preparation and Measurement Techniquescontrasting
confidence: 57%
“…Subsequently, stacks sandwiched between two thermally-well-conducting substrates were created for a more efficient heat exhaust, and the highest emission frequency was increased gradually [25][26][27]. In addition, Tsujimoto et al [32] observed an increase of the maximum emission frequency for Pb-doped BSCCO stacks and argued that the higher interlayer critical current density j c leads to an increase of the Josephson plasma frequency, which most likely determines the cutoff frequency of emission. However, for high operating temperatures above 70 K, the reported BSCCO terahertz emitters always either have no emission or radiate at a frequency well below 500 GHz [25][26][27]29,35], limiting their applicability.…”
Section: Introductionmentioning
confidence: 99%
“…A solid line represents fe ∝ √ Jc. Data correspondences are A07 [29], A11 [104], I12 [91], I13 [113], K15-1 [105], K15-2 [114], N10 [94], N12 [87], N14 [32], T09 [89], T12-1 [96], T12-2 [86], T14 [110], T15-1 [33], and T15-2 [34]. specific device.…”
Section: Suitable Materialsmentioning
confidence: 99%
“…The most typical Bi-based cuprate superconductors are Bi2201 (n = 1, Michel et al 1987), Bi2212 (n = 2, von Schnering et al 1988), and Bi2223 (n = 3, Takano et al 1988), whose critical transition temperature (T c ) can arrive at 20 K, 90 K, and 110 K, respectively [5][6][7]. Therein, Bi2212 superconductor is expected to be applied in terahertz technology due to its intrinsic Josephson effect and excellent performance owing to its excellent service behavior at low temperature in strong magnetic field [8][9][10]. In addition, since Bi2212 superconducting tapes, wires, and films have been utilized widely in superconductivity and related fields, they have attracted great attention from the academics and industry [11][12][13].…”
Section: Introductionmentioning
confidence: 99%